2015
DOI: 10.1016/j.ssi.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Conducting interfaces between amorphous oxide layers and SrTiO3(110) and SrTiO3(111)

Abstract: Interfaces between (110) and (111)SrTiO 3 (STO) single crystalline substrates and amorphous oxide layers, LaAlO 3 (a-LAO), Y:ZrO 2 (a-YSZ), and SrTiO 3 (a-STO) become conducting above a critical thickness t c . Here we show that t c for a-LAO is not depending on the substrate orientation, i.e. t c (a-LAO/(110)STO) ≈ t c (a-LAO/(111)STO) interfaces, whereas it strongly depends on the composition of the amorphous oxide: t c (a-LAO/(110)STO) < t c (a-YSZ/(110)STO) < t c (a-STO/(110)STO). It is concluded that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…So far, generating oxide 2DEGs by redox reactions has been largely limited to the STO substrate, for which various capping layers have been adopted, such as a-LAO, 22 amorphous CaHfO3, 20 yttria-stabilized zirconia (YSZ), 18 and Al2O3. 4,19 Besides (001)-oriented STO substrates, STO with orientations of (110) and (111) 27 has also been used for the deposition of a-LAO. Recently, Sarkar et al 28 replaced the STO substrate of a-LAO/STO heterostructures with anatase TiO2 [TiO2(A)] and rutile TiO2 [TiO2(R)] and obtained interfacial 2DEGs with different transport properties from a-LAO/STO.…”
Section: Introductionmentioning
confidence: 99%
“…So far, generating oxide 2DEGs by redox reactions has been largely limited to the STO substrate, for which various capping layers have been adopted, such as a-LAO, 22 amorphous CaHfO3, 20 yttria-stabilized zirconia (YSZ), 18 and Al2O3. 4,19 Besides (001)-oriented STO substrates, STO with orientations of (110) and (111) 27 has also been used for the deposition of a-LAO. Recently, Sarkar et al 28 replaced the STO substrate of a-LAO/STO heterostructures with anatase TiO2 [TiO2(A)] and rutile TiO2 [TiO2(R)] and obtained interfacial 2DEGs with different transport properties from a-LAO/STO.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, strong redox reactions can occur when growing perovskite oxides (ABO3) capping films having B site cations of Al, Ti, Zr, and Hf or other elements with a heat of metal oxide formation lower than -350 kJ per mole of oxygen, and a work function, φ, in the range of 3.75 eV < φ < 4.4 eV 21,22 . The room temperature synthesis generally leads to disordered (d) or amorphous-like film growth, and 2DELs have been observed for heterostructures of STO capped with disordered LaAlO3 (d-LAO), disordered yttria-stabilized zirconia (d-YSZ), and disordered strontium titanate (d-STO) 16,21,[23][24][25] . This approach is applicable to not only (001)-oriented but also (110) and (111)-oriented STO crystals 25 .…”
mentioning
confidence: 99%
“…The room temperature synthesis generally leads to disordered (d) or amorphous-like film growth, and 2DELs have been observed for heterostructures of STO capped with disordered LaAlO3 (d-LAO), disordered yttria-stabilized zirconia (d-YSZ), and disordered strontium titanate (d-STO) 16,21,[23][24][25] . This approach is applicable to not only (001)-oriented but also (110) and (111)-oriented STO crystals 25 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15][16][17][18] Later on, formation of 2DEG has been realized by capping STO substrate with non-polar amorphous LAO, STO and yttria-stabilized zirconia. [12,19,20] However, this approach requires the use of techniques, such as pulsed laser deposition or molecular beam epitaxy, which are expensive to be implemented on industrial scales. Despite that, previous studies showed that the atomic layer deposition method has already been used to create all-oxide transistors with outstanding high-frequency characteristics.…”
Section: Introductionmentioning
confidence: 99%